Approach to strategy and enterprise size - Radomska Joanna (Management)
The article describes the subject of approach to strategy based on the current classification differentiating five types of approach specified on the basis of three features relating to business environment, such as predictability (ability to forecast), malleability (ability to shape) and harshness (ability to survive). The research demonstrated the existence of a correlation between the approaches and the size of an enterprise, indicating that small organisations most often apply a classical and renewal strategy. Medium-sized companies, however, are characterised by a low pressure on visionary behaviour and the shaping of the boundaries of the business environment. They therefore select most often a classical and adaptive approach. Large enterprises, according to the assumptions made, most often demonstrate the ability to change the conditions of competitive struggle and create new markets by showing a visionary approach.